2023
DOI: 10.1002/smtd.202201712
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic‐Cell‐Based Multi‐Compartmentalized Hierarchical Systems

Abstract: In the extant lifeforms, the self‐sustaining behaviors refer to various well‐organized biochemical reactions in spatial confinement, which rely on compartmentalization to integrate and coordinate the molecularly crowded intracellular environment and complicated reaction networks in living/synthetic cells. Therefore, the biological phenomenon of compartmentalization has become an essential theme in the field of synthetic cell engineering. Recent progress in the state‐of‐the‐art of synthetic cells has indicated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 187 publications
0
7
0
Order By: Relevance
“…Consequently, various coacervates have been explored as models for artificial membraneless organelles, , and the construction of coacervate-in-vesicle structures has become a key area of research in advancing artificial cell models. , A pioneering work that utilized coacervate-in-vesicle structures for an artificial cell model can be found from the report demonstrating the transformation of polyelectrolyte/ribonucleotide-enriched coacervate droplets into membrane-bound vesicles . Exploiting the ability of coacervate droplets to concentrate organic dyes, proteins, and nanoparticles within an aqueous lumen, the authors demonstrated the coupling of enzyme cascade reactions that are generated within single vesicles.…”
Section: Fabrication Of Multicompartment Synthetic Vesiclesmentioning
confidence: 99%
“…Consequently, various coacervates have been explored as models for artificial membraneless organelles, , and the construction of coacervate-in-vesicle structures has become a key area of research in advancing artificial cell models. , A pioneering work that utilized coacervate-in-vesicle structures for an artificial cell model can be found from the report demonstrating the transformation of polyelectrolyte/ribonucleotide-enriched coacervate droplets into membrane-bound vesicles . Exploiting the ability of coacervate droplets to concentrate organic dyes, proteins, and nanoparticles within an aqueous lumen, the authors demonstrated the coupling of enzyme cascade reactions that are generated within single vesicles.…”
Section: Fabrication Of Multicompartment Synthetic Vesiclesmentioning
confidence: 99%
“…Multicompartmentalization is a key feature of living cells, within which many subcompartments reside to perform a host of highly specialized biological functions . Such a unique structure provides many confined spaces to separate incompatible biomolecules or opposing reagents and to perform multistep metabolic reactions.…”
Section: Introductionmentioning
confidence: 99%
“…Such a unique structure provides many confined spaces to separate incompatible biomolecules or opposing reagents and to perform multistep metabolic reactions. Over the past two decades, to mimic the structure and function of cells, various artificial multicompartmentalized microreactors for hosting multiple catalysts have been developed, such as emulsions, multiple emulsions, coacervate, , liposomes, , polymersomes, , proteinosomes, , multicompartmentalized hydrogels, and inorganic particles. Despite remarkable progress, critical limitations remain in view of practical catalytic applications of these systems. This is because that most of these reported multicompartmentalized structures are essentially soft matter systems with insufficient mechanical strength and chemical robustness, thereby being unable to use in industrially preferred continuous flow catalysis. , Although inorganic materials exhibit sufficient mechanical stability, their small particle size (nano-to-submicron scales) makes them impossible to directly use in practical continuous flow catalysis .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The design and construction of integrated chemical ensembles for mimicking exquisite attributes of living cells attract considerable interest in different research communities. Biocompartmentalization with functionalized membranes is a prerequisite step toward the design and construction of artificial cell-like microstructures. , Over the past years, strategies toward membrane-delineated compartmentalization have been widely developed focusing on the use of a diverse range of amphiphilic building blocks that underwent spontaneous or directed assembly in aqueous solutions or oil/water mixtures to produce microcompartments including liposomes, , polymersomes, colloidosomes, , proteinosomes, as well as membranized coacervates which successfully showed various biological processes such as in vitro gene expression, chemical communication, biomacromolecule phase separation, modulated membrane permeability, and enzymatic reactions, as well as a wide variety of dynamic behaviors including proliferation, differentiation, fusion, , predation, and exocytosis . Despite these significant advancements in demonstrating advanced cell-like behaviors and functionalities, the composition of the microcompartmental chassis remains quite limited.…”
Section: Introductionmentioning
confidence: 99%